Improving Knowledge and Skills of Posyandu Cadres in Identifying Stunting in Sei Glugur Village 2024 - Mangkuji, Betty; Siregar, Yusniar; Sitepu, Jujuren Br. (Asian Journal of Community Services, 2024)
Community service activities aim to increase the knowledge and skills of posyandu cadres how to measure body weight and body length / height of toddlers how to practice filling KMS. The method of community service is counseling on stunting and how to identify stunting infants, toddlers with lectures, discussions, and demonstrations of making KMS filling. And counseling is evaluated pre-test and post-test, and role play and demonstration during posyandu.  The results obtained after community service from 36 cadres before training were low knowledge 80.6%, sufficient 13.9% and good 5.5% and after being given counseling the results were good knowledge 88.9% and sufficient 8.3% and less 8.3%. And the skills to fill KMS before being given training the majority of filling is not right 94.4%, the minority is right 5.5%. After the training the majority of cadres were right filling KMS 91.7% and not right 8.3%.